3D-Printed Carbon Nanoelectrodes for In Vivo Neurotransmitter Sensing - Cao, Qun (Nano Lett, 2020)
Direct laser writing, a nano 3D-printing approach, has enabled fabrication of customized carbon microelectrode sensors for neurochemical detection. However, to detect neurotransmitters in tiny biological organisms or synapses, sub-micron nanoelectrodes are required. In this work, we used 3D-printing to fabricate carbon nanoelectrode sensors. Customized structures were 3D-printed and then pyrolyzed, resulting in free-standing carbon electrodes with nanotips. The nanoelectrodes were insulated with atomic layer deposition of Al(2)O(3) and the nanotips were polished by focused ion beam to form 600 nm disks. Using fast-scan cyclic voltammetry, the electrodes successfully detected stimulated dopamine in adult fly brain, demonstrating they are robust and sensitive to use in tiny biological systems. This work is the first demonstration of 3D-printing to fabricate free-standing carbon nanoelectrode sensors, and will enable batch-fabrication of customized nanoelectrode sensors with precise control and excellent reproducibility.